War-related continuous traumatic stress as a potential mediator of associations between moral distress and professional quality of life in nurses: a cross-sectional study in Ukraine - Larysa Zasiekina; Anastasiia Martyniuk (BMC Nursing)
Abstract Background At the beginning of 2022, Central Europe entered a state of emergency due to the Russian invasion of Ukraine. Nurses were particularly vulnerable to a decline in their professional quality of life, facing repeated exposure to military trauma, ethical dilemmas, prolonged working hours, and increased stress and fatigue. This study aimed to contribute to our understanding of the potential mediating effect of war-related continuous traumatic stress on the association between moral distress and professional quality of life, including compassion satisfaction and compassion fatigue, represented by burnout and secondary traumatic stress. Methods This study used the Professional Quality of Life (ProQOL) Scale to assess compassion fatigue, including burnout, secondary traumatic stress, and compassion satisfaction; the Moral Distress Questionnaire for Nurses to examine everyday moral distress in healthcare facilities and everyday ethical dilemmas of nurses; and the Continuous Traumatic Stress Response (CTSR) Scale to assess ongoing threats, resulting in exhaustion/rage, and fear/betrayal. The sample consisted of 130 female nurses (mean age 40.20 ± 12.15 years) from general surgery, neurosurgery, trauma and orthopaedic surgery, and urgent care who had been undergoing advanced training to work with injured military personnel at the Volyn Medical Institute (Ukraine) from March to May 2023. All nurses had experienced direct and indirect exposure to military trauma, and 105 participants were working with injured military personnel. Results The results of the mediation analysis indicated that war-related continuous traumatic stress fully mediated the relationship between moral distress and different components of professional quality of life, namely, compassion fatigue, including burnout and secondary traumatic stress, and compassion satisfaction. Conclusion Research has shown that continuous traumatic stress has a significant effect on the relationship between moral distress and various aspects of professional quality of life, underscoring the need for targeted interventions for nurses facing war-related trauma.